Heart rate and blood lactate response along with grip strength deterioration during successive judo simulations (randori) - Sarkar, S.; Ganguly, S.; Medabala, T. (Trends in Sport Sciences, 2024)
Introduction: Judo requires highly technical and tactical skills with physiological response optimization to succeed.